2021
DOI: 10.30900/kafkasegt.941467
|View full text |Cite
|
Sign up to set email alerts
|

Examining 21st century skills of 3-6 years old children in terms of some variables

Abstract: In the changing world, it is seen that it is important to acquire skills such as creativity, critical thinking, problem solving, communication and cooperation, which are accepted as 21st century skills, at an early age. This study aims to examine the 21st-century skills of 3-6-year-old preschool children in terms of some variables. Relational screening model was used in the study. The research was carried out with 1055 children selected from different independent kindergartens and kindergartens affiliated to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…According to researchers, one of the organizations that conduct the most research on the twenty-first-century skills is the Partnership for 21 st -Century Skills (P21) (Dinler, Simsar & Yalçın, 2021 ; Göksün & Kurt, 2017 ; Yalçın et al, 2020 ). P21 deals with the twenty-first-century skills under three main headings: life and career skills; learning and innovation skills; and information, media and technology skills (Partnership for 21s t-century Skills, 2018a ; 201 8b ; 2015 ).…”
Section: Twenty-first-century Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to researchers, one of the organizations that conduct the most research on the twenty-first-century skills is the Partnership for 21 st -Century Skills (P21) (Dinler, Simsar & Yalçın, 2021 ; Göksün & Kurt, 2017 ; Yalçın et al, 2020 ). P21 deals with the twenty-first-century skills under three main headings: life and career skills; learning and innovation skills; and information, media and technology skills (Partnership for 21s t-century Skills, 2018a ; 201 8b ; 2015 ).…”
Section: Twenty-first-century Skillsmentioning
confidence: 99%
“…The reviewed literature has shown that there are many studies on the twenty-first-century skills, STEM and design thinking (Akgündüz & Akpınar, 2018 ; Dinler, Simsar & Yalçın, 2021 ; Menial & Leifer, 2011 ; Uluyol & Eryılmaz, 2015 ; Yalçın & Erden, 2021 ; Yalçın & Öztürk, 2022 ; Yalçın, 2020 ). The given studies reported that STEM activities increased the frequency of asking questions (Haden et al, 2014 ) and developed self-efficacy, interest in science, spatial visualization and mental rotation skills (Lamb et al, 2015 ), besides developing goal-oriented design, problem-solving thinking, innovation, pattern repetition and design testing skills (Bagiati & Evangelou, 2016 ).…”
Section: Twenty-first-century Skillsmentioning
confidence: 99%